KAJIAN PEMIKIRAN KI HAJAR DEWANTARA TENTANG KARAKTER BANGSA DAN PENDIDIKAN KEBANGSAAN, 2017 - Mentari, Ana
Tesisiniberjudul"PemikiranKi HajarDewantaratentangkarakterbangsadanpendidikankebangsaan". Penulismengharapkanmelaluihasilpenelitiantesis yang penulisbuatmampumemberikanmanfaatbagimahasiswadanmasyarakatumummengenaipemikiran Ki HajarDewantara. Metode yang digunakanadalahmetodehistoris, denganpendekatankualitatif, karenabertujuanmenuangkanhasilkajianberdasarkanargumentasidanpemahaman yang mendalamsecaradeskripsi. Metodehistorisadalahsuatu proses mengujidanmenganalisissecarakritisrekamanpeninggalan masa lampau. Sehinggadalamhalini, penelitiakanmelakukanpengujiandananalisisterhadapsumber-sumber yang berhubungandengankajian yang penelitibahas. Langkah-langkahdalammetodehistorisiniterdiridari, heuristik, kritiksumber, interpretasi, danhistoriografi. Masalahutamadalamtesisiniterbagikedalamempatpertanyaanpenelitiandiantaranya, 1) Bagaimanapokok-pokokpemikiran Ki HajarDewantaratentangkarakterdanpendidikankebangsaan di Indonesia?, 2) Sumber-sumberpemikiranapa yang menginspirasipemikiran Ki HajarDewantara?, 3) Bagaimanaimplementasipemikiran Ki HajarDewantaratentangkarakterdanpendidikankebangsaanterhadappendidikan di Indonesia?, 4) Bagaimanarelevansipemikirankarakterdanpendidikankebangsaan Ki HajarDewantaradalamkeilmuanpendidikankewarganegaraan?. Ki HajarDewantaramengungkapkanbahwa, "pendidikannasionalseharusnyamenimbulkan rasa cintaterhadapkebudayaandankebatinan (mental culture) sendiri". Beliau juga mengungkapkanbahwa, a) pengajaranrakyatharuslahbersemangatkeluhuranbudimanusia; karenanyaharusmementingkansegalanilaikebatinan (mental culture) danmenghidupkansemangat idealism; b) pengajaranrakyatharusmendidikkearahkecerdasanbudipekerti, yaknimatangnyajiwaseutuhnya (character building); c) pengajaranrakyatharusmendidikkearahkekeluargaan, yaknimerasabersama-samahidup, bersama-samasusahdansenang, bersama-samatanggungjawab, dsb; mulaikekeluargaandalamlingkungankecil, sampaikekeluargaan yang besar (misalnyakekeluargaanbangsa-bangsa). Pendidikankarakterharusdilaksanakandenganngerti-ngroso-nglakoni (menyadari, menginsyafi, danmelakukan). Ki HajarDewantaramenggunakan kata karakterdengan kata lain yaknibudi-pekerti, yang bermaknaperpaduangerakantarafikiran, perasaandankehendak yang menghasilkantenaga. Sedangkanpendidikankebangsaanmerupakanpendidikan yang berlandaskanakankebudayaanbangsa. Kata kunci:Ki HajarDewantara, Karakter, PendidikanKebangsaan;--- This thesis entitled "Ki HajarDewantara's thoughts on character and national awareness education". The authors expected through the thesis research,she could be able to provide benefits for students and the general public about the thoughts of Ki HajarDewantara. The method used was the historical method, using a qualitative approach, aimed to pour the results of the study based on intensive argumentation and in-depth understanding of a description. The historical method was a process of examining and critically analyzing the recording of the past relic. So in this case, researchers conducted testing and analysis of the sources related to the study that researchers discussed. The steps in this historical method consisted of, heuristics, source criticism, interpretation, and historiography. The main problem in this thesis was divided into four research questions i.e.: 1) How were the main points of Ki HajarDewantara's thoughts about the character and education of nationhood in Indonesia?, 2) What sources of thought inspired Ki HajarDewantara's thinking?, 3) How to implemented thinking Ki HajarDewantara about the character and education of nationality towards education in Indonesia?, 4) How was the relevance of character thinking and national education Ki HajarDewantara in the scholarship of civic education?. Ki HajarDewantararevealsed that, "National education should generate a sense of love for culture and mental culture itself." He also revealsed that a) the teaching of the people must be passionate to the virtues of man; Therefore if must attach the importance to all the values of mental culture and enliven the spirit of idealism; b) the teaching of the people must educate towards the intelligence of character, the maturation of the whole soul (character building); c) the teaching of the people should educate them toward kinship, that was to feel together life, together with hard and happy, together responsibility, etc.; begin kinship in small environments, to large the families (eg, the kinship of nations). Character education should be done with ngerti-ngroso-nglakoni (realize, come to realize, and do).Ki HajarDewantara uses the word character in other words ie mind-pekerti, which means a blend of motion between the mind, feelings, and wills that generate energy. While the education of nationality was an education based on the nation's culture. Keywords: Ki HajarDewantara, Character, National Awarness Education